Deodorizing adhesive layer for packaging bag

By using nanozerite and transition metal modified adhesive on the packaging bag to form the deodorizing adhesive layer, the problems of complex manufacturing process and inflexible deodorization film in the prior art are solved, and the effect of efficient deodorization and smooth coating is achieved.

JP2025043524APending Publication Date: 2025-04-01KYODO PRINTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023150842
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When the prior art provides deodorization function for packaging bags, the manufacturing process is complicated and the deodorization film is not flexible enough. The commercial deodorizer has a large particle size, resulting in unsmooth coating, adhesion and appearance problems.

Method used

Nanozeolites and adhesives with transition metals are used to form an efficient deodorizing adhesive layer. Through the combination of nanoparticle sized Zeolites and transition metals, the deodorization performance and coating smoothness are improved.

Benefits of technology

The efficient deodorization performance of the deodorizing adhesive layer on the packaging bag is achieved, ensuring the smoothness and adhesion of the layer, avoiding appearance problems, and simplifying the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043524000001_ABST
    Figure 2025043524000001_ABST
Patent Text Reader

Abstract

To provide a deodorizing adhesive layer that exhibits superior deodorizing performance and surface smoothness.SOLUTION: A deodorizing adhesive layer for packaging bags comprises: a nanozeolite doped with a transition metal; and an adhesive, wherein the coating amount is 10.0 g / m2 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a deodorant adhesive layer for use in packaging bags. [Background technology]

[0002] Foodstuffs, medicines, medical instruments, etc. may be subjected to heat sterilization treatment while sealed in a packaging bag. Also, foodstuffs may be cooked by heating while sealed in a packaging bag before being consumed.

[0003] When the contents are heated while sealed in a packaging bag, the contents themselves, the packaging material, or both may emit an unpleasant odor. The source of the unpleasant odor is thought to be denatured substances such as hydrocarbons, oils and fats, and proteins. Among these unpleasant odors, the protein denaturation odor, and especially the sulfur odor (the odor caused by sulfur compounds), are often problematic.

[0004] Furthermore, in the case of medicines, supplements, etc., the unpleasant odor inherent to the substances themselves can be a problem even if they are not heated.

[0005] In an attempt to absorb and eliminate such unpleasant odors, various packaging bag materials including a deodorant layer have been proposed in the prior art.

[0006] For example, Patent Document 1 describes a laminate for heat sterilization treatment, which includes a base layer and a sealant layer, and contains hydrophobic zeolite in the sealant layer. It explains that in this laminate, the hydrophobic zeolite in the sealant layer exerts an adsorption effect on odorous components.

[0007] Furthermore, Patent Document 2 describes an odor-capturing laminate adhesive resin composition that contains a base agent and a curing agent for a two-component adhesive, as well as a hydrogen sulfide-capturing pigment such as zinc oxide, and a diluent (organic solvent), and describes the use of this adhesive resin composition to produce a packaging bag with odor-capturing properties. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2019-177518 A [Patent Document 2] JP 2020-164587 A Summary of the Invention [Problem to be solved by the invention]

[0009] As in Patent Document 1, imparting a deodorizing function to any of the layers constituting the laminate for packaging bags is considered to be an effective means for adsorbing and removing unpleasant odors. However, this method requires kneading a deodorant into the resin to produce a deodorant film. Therefore, packaging bags containing deodorant films have a complicated manufacturing process, and the deodorant film produced lacks versatility.

[0010] In contrast, as described in Patent Document 2, a method in which an adhesive containing a deodorizer is prepared, the adhesive is used to manufacture a laminate for packaging bags, and a deodorizing adhesive layer is formed between the layers is simple and is considered to be a versatile adhesive.

[0011] However, deodorants applicable to packaging bags are generally commercially available as large particle diameter particles, and therefore adhesives containing commercially available deodorants have insufficient coating properties, and the deodorant adhesive layer formed has poor smoothness, which leads to poor adhesion with adjacent layers and poor appearance of the packaging bag.

[0012] Therefore, an object of the present invention is to provide a deodorizing adhesive layer that is excellent in deodorizing properties and smoothness, and a laminate for packaging bags that includes the deodorizing adhesive layer. [Means for solving the problem]

[0013] The present invention is as follows.

[0014] Aspect 1: A method for producing a composition comprising a nano-zeolite doped with a transition metal and an adhesive, Coating weight: 10.0g / m 2 Below is the Deodorizing adhesive layer for packaging bags. Aspect 2: The deodorizing adhesive layer according to aspect 1, wherein the average particle size of the nano zeolite is 5 nm or more and 500 nm or less. Aspect 3: The deodorizing adhesive layer according to aspect 1, wherein the SAR of the nano zeolite is 20 or less. Aspect 4: The deodorizing adhesive layer according to aspect 2, wherein the SAR of the nano zeolite is 20 or less. Aspect 5: The deodorizing adhesive layer according to aspect 1, wherein the transition metal is one or more selected from Ag, Cu, and Zn. Aspect 6: The deodorizing adhesive layer according to aspect 1, wherein the adhesive is one or two types selected from an ester-based adhesive and an ether-based adhesive. Aspect 7: An odor-eliminating adhesive comprising a transition metal-doped nanozeolite and an adhesive. Aspect 8: The deodorizing adhesive according to aspect 7, which is used to form the deodorizing adhesive layer according to aspect 1. Aspect 9: A laminate for a packaging bag, comprising a substrate layer, the deodorizing adhesive layer described in aspect 1, and a sealant layer. Aspect 10: The laminate for a packaging bag according to aspect 9, further comprising one or two layers selected from a barrier layer and a reinforcing layer. Aspect 11: A method for producing the packaging bag laminate according to aspect 9 or 10, comprising: The method includes using the deodorant adhesive according to embodiment 7 for bonding at least one layer between the layers. A method for manufacturing a laminate for a packaging bag. Effect of the Invention

[0015] According to the present invention, there are provided a deodorizing adhesive layer having excellent deodorizing properties and smoothness, and a laminate for packaging bags including said deodorizing adhesive layer. [Brief description of the drawings]

[0016] [Figure 1] 1 is a schematic cross-sectional view showing an example of an embodiment of the packaging bag laminate of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one example of another embodiment of the packaging bag laminate of the present invention.

[0017] Deodorizing adhesive layer for packaging bags The deodorant adhesive layer for packaging bags of the present invention contains nano zeolite doped with a transition metal and an adhesive, and has a coating weight of 10.0 g / m 2 The following is the result.

[0018] In the present invention, a nano-zeolite doped with a transition metal is used as a deodorant.

[0019] Zeolite doped with transition metals has a high affinity with polar compounds and an expanded pore size, so it has excellent adsorption properties for sulfur compounds, for example. In addition, since it is nano-zeolite with a small particle size, the deodorant adhesive layer containing it has excellent smoothness. Due to these factors, the deodorant adhesive layer for packaging bags of the present invention functions as an adhesive layer that is particularly excellent in adsorption properties for sulfur compounds, even though it is a thin layer.

[0020] In addition, since the deodorant adhesive layer of the present invention has excellent smoothness, the occurrence of defective appearance is suppressed, and when formed into a laminate for packaging bags, it has the advantage of having excellent adhesion to adjacent layers.

[0021] Furthermore, the deodorant adhesive layer of the present invention contains nano zeolite with a small particle size, and is a thin layer with excellent smoothness, so it has excellent transparency. Therefore, if the deodorant adhesive layer of the present invention is laminated with a transparent resin layer to form a laminate for a packaging bag, a packaging bag with excellent visibility of the contents can be obtained.

[0022] Hereinafter, each element constituting the deodorant adhesive layer for packaging bags of the present invention will be described in order.

[0023] <Nanozeolite doped with transition metals> The odor eliminating adhesive layer for packaging bags of the present invention contains nano zeolite doped with a transition metal.

[0024] The zeolite contained in the deodorizing adhesive layer for packaging bags of the present invention may have pores defined by eight-membered rings, and its skeletal structure may be, for example, AEI, AFT, AFX, CHA, DDR, ERI, ITE, ITW, KFI, LEV, LTA, MER, PAU, RHO, UFI, etc.

[0025] The zeolite contained in the deodorant adhesive layer for packaging bags of the present invention may be a hydrophilic zeolite. The hydrophilicity of zeolite is indicated by the silica-alumina ratio (SAR, SiO2 / Al2O3 molar ratio), and the larger this value is, the higher the hydrophobicity is, and the smaller this value is, the higher the hydrophilicity is. The SAR of the zeolite in the present invention may be 20 or less, 15 or less, 10 or less, 8.0 or less, 5.0 or less, 3.0 or less, or 2.0 or less. There is no restriction on the lower limit of the SAR, but generally, it is difficult to synthesize a zeolite with a SAR of less than 1. From this viewpoint, the SAR of the zeolite contained in the deodorant adhesive layer for packaging bags of the present invention may be 0.8 or more, 0.9 or more, or 1.0 or more.

[0026] In addition, in adhesives containing a deodorant in the prior art, the deodorant adsorbs the organic solvent contained in the adhesive as a diluent, causing the adsorption sites for unpleasant odors to become blocked, and the resulting packaging bag cannot exhibit the desired deodorizing function, resulting in insufficient deodorizing properties.

[0027] In contrast, when the transition metal-doped zeolite used in the present invention is hydrophilic, the deodorizing performance is maintained without being affected by the organic solvent contained in the adhesive. Therefore, the deodorizing adhesive layer for packaging bags of this embodiment can be easily formed by a normal coating method using the deodorizing adhesive described below. Therefore, according to the present invention, a high level of deodorizing performance can be obtained without the need to manufacture a dedicated deodorizing film, and the manufacturing process of the packaging bag containing the deodorizing adhesive layer for packaging bags of the present invention is simplified.

[0028] The zeolite contained in the deodorant adhesive layer for packaging bags of the present invention is doped with a transition metal. The transition metal doped in the zeolite of the present invention may be, for example, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ru, Rh, Pd, Ag, Ce, Zn, etc., and may be one or more selected from Ag, Cu, and Zn.

[0029] The doping amount of the transition metal, relative to the Al atoms contained in the zeolite, may be, for example, 10 mol% or more, 15 mol% or more, 20 mol% or more, 25 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, or 55 mol% or more, and may be less than 100 mol%, 95 mol% or less, 90 mol% or less, 80 mol% or less, 70 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, or 45 mol% or less.

[0030] When the transition metal is Ag, the doping amount may be, for example, 20 mol% or more or 25 mol% or more, and, for example, 60 mol% or less or 55 mol% or less, based on the Al atoms contained in the zeolite.When the transition metal is Cu, the doping amount may be, for example, 50 mol% or more or 55 mol% or more, and, for example, less than 100 mol% or 95 mol% or less, based on the Al atoms contained in the zeolite.When the transition metal is Zn, the doping amount may be, for example, 10 mol% or more or 15 mol% or more, and, for example, 50 mol% or less or 45 mol% or less, based on the Al atoms contained in the zeolite.

[0031] Doping of the zeolite with the transition metal may be carried out, for example, by known ion exchange methods.

[0032] The zeolite contained in the deodorant adhesive layer for packaging bags of the present invention is nano-zeolite with a small particle size.The average particle size of the nano-zeolite may be, for example, 5 nm or more, 10 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, or 40 nm or more, and may be, for example, 500 nm or less, 400 nm or less, 300 nm or less, 250 nm or less, 200 nm or less, 150 nm or less, 100 nm or less, or 80 nm or less.

[0033] The above average particle size is a particle size at which the cumulative mass percentage is 50% in the particle size distribution obtained by a laser diffraction method measured in accordance with JIS Z8825:2022.

[0034] The content of zeolite in the deodorizing adhesive layer for packaging bags of the present invention may be, for example, 1 mass% or more, 3 mass% or more, 5 mass% or more, or 7 mass% or more, based on the total mass of the deodorizing adhesive layer, and may be, for example, 25 mass% or less, 20 mass% or less, 15 mass% or less, 12 mass% or less, or 10 mass% or less.

[0035] The content of zeolite in the deodorant adhesive layer is, for example, 0.05 g / m in terms of the mass of zeolite per unit area of ​​the adhesive layer. 2 More than 0.10g / m 2 or more, or 0.15 g / m 2 or more, for example, 4.0 g / m 2 Below 3.0g / m 2 Below 2.0g / m 2 Below 1.5g / m 2 Below 1.2g / m 2 Below, 0.8g / m 2 Less than or equal to 0.5g / m 2 It may be the following:

[0036] <glue> The deodorizing adhesive layer for packaging bags of the present invention contains an adhesive.

[0037] The adhesive contained in the deodorant adhesive layer for packaging bags of the present invention may be appropriately selected from adhesives for packaging bags, particularly known as dry laminate adhesives. The adhesive may be selected from, for example, ester-based adhesives, ether-based adhesives, etc. The laminate for packaging bags to which the deodorant adhesive layer of the present invention is applied is premised on the heat treatment of the contents. Therefore, the adhesive contained in the deodorant adhesive layer of the present invention may be one with high heat resistance, particularly a two-liquid type ester-based adhesive.

[0038] The content of the adhesive in the deodorizing adhesive layer for packaging bags of the present invention may be, for example, 75 mass% or more, 80 mass% or more, 85 mass% or more, 88 mass% or more, or 90 mass% or more, based on the total mass of the deodorizing adhesive layer, and may be, for example, 99 mass% or less, 97 mass% or less, 95 mass% or less, 93 mass% or less, or 90 mass% or less.

[0039] <Optional ingredients> The deodorant adhesive layer for packaging bags of the present invention includes a transition metal-doped nano zeolite and an adhesive. The deodorant adhesive layer may contain optional components other than these. The optional components in the deodorant adhesive layer may be, for example, a filler, a colorant, a defoamer, an antiaging agent, etc.

[0040] <Coating amount of deodorant adhesive layer for packaging bags> The deodorizing adhesive layer for packaging bags of the present invention is a deodorizing layer that is excellent in adsorption properties, particularly for sulfur compounds, even though it is a thin layer.

[0041] The coating amount of the deodorant adhesive layer for packaging bags of the present invention is, for example, 0.7 g / m2 as a mass per unit area. 2 More than 0.8g / m 2 More than 1.0g / m 2 More than 2.0g / m 2 or more than 3.0g / m 2 or more, for example, 10.0 g / m 2 Below 8.0g / m 2 Below 5.0g / m 2 Below 4.0g / m 2 Below 3.0g / m2 Below 2.0g / m 2 Less than or equal to 1.5g / m 2 It may be the following:

[0042] The thickness of the deodorant adhesive layer for packaging bags of the present invention may be approximately 0.1 μm or more or 1 μm or more, and may be 5 μm or less or 10 μm or less.

[0043] Deodorizing adhesive According to another aspect of the present invention, there is provided an odor-eliminating adhesive.

[0044] The deodorant adhesive of the present invention contains a transition metal-doped nanozeolite and an adhesive, and may further contain a diluent and other optional components.

[0045] The deodorant adhesive of the present invention is preferably used to form the deodorant adhesive layer for packaging bags of the present invention.Therefore, the type of transition metal-doped nano zeolite and adhesive contained in the deodorant adhesive of the present invention may be the same as the zeolite and adhesive contained in the desired deodorant adhesive layer for packaging bags.The ratio of zeolite and adhesive in the deodorant adhesive may also be the same as the ratio of zeolite and adhesive in the desired deodorant adhesive layer for packaging bags.

[0046] The diluent contained in the deodorant adhesive is not particularly limited as long as it can disperse the transition metal-doped nano zeolite and dissolve the adhesive. The diluent may be an organic solvent, and may be one or more selected from, for example, esters, alcohols, ketones, ethers, hydrocarbons, etc.

[0047] Examples of esters include ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, and isoamyl acetate; Examples of alcohols include methanol, ethanol, n-propanol, and isopropanol; Examples of ketones include acetone, methyl ethyl ketone, methyl-n-butyl ketone, and methylcyclohexanone; Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monoethyl ether acetate; Examples of hydrocarbons include toluene, xylene, and n-hexane; Examples of each can be given.

[0048] The amount of diluent may be appropriately set by a person skilled in the art so that the deodorant adhesive has an appropriate viscosity depending on the coating method to be adopted. The amount of diluent may be, for example, 10% by mass or more or 20% by mass or more, and may be, for example, 90% by mass or less, or 80% by mass or less, based on the total mass of the deodorant adhesive.

[0049] The optional components contained in the deodorant adhesive of the present invention may be those contained in the desired deodorant adhesive layer as well as those normally contained in adhesives. Such optional components may be, for example, plasticizers, tackifiers, fillers, thickeners, colorants, pH adjusters, antioxidants, preservatives, etc.

[0050] 《Laminated body for packaging bags》 According to yet another aspect of the present invention, a laminate for a packaging bag is provided.

[0051] The laminate for packaging bags of the present invention includes a substrate layer, the deodorant adhesive layer of the present invention, and a sealant layer. The laminate for packaging bags may further include one or two layers selected from a barrier layer and a reinforcing layer.

[0052] The base layer may be made of a material appropriately selected from materials that can exhibit the necessary physical properties when made into a packaging bag, and may be made of one or more materials selected from, for example, polyethylene terephthalate, polypropylene, nylon, paper, aluminum foil, etc.

[0053] The barrier layer has the role of protecting the contents of the packaging bag from the environment outside the bag, and may have the function of blocking, for example, oxygen, moisture, etc. The barrier layer may be made of, for example, aluminum foil, metal-vapor-deposited nylon film, silica-vapor-deposited nylon film, metal-vapor-deposited polyethylene terephthalate film, silica-vapor-deposited polyethylene terephthalate film, etc.

[0054] The reinforcing layer has the role of imparting strength, durability, etc. to the packaging bag. The reinforcing layer may be made of, for example, nylon, oriented polypropylene, polyethylene terephthalate, or the like.

[0055] The sealant layer has a heat-sealing ability, and has the function of forming and maintaining the shape of the packaging bag and sealing the contents. The sealant layer may be made of, for example, polyolefin. When the laminate for packaging bags of the present invention is intended to heat-treat the contents, the sealant layer is preferably made of unstretched polypropylene, which has excellent heat-sealing ability and excellent heat resistance. On the other hand, when the laminate for packaging bags of the present invention is not intended to heat-treat the contents, there is no restriction on the sealant layer in terms of heat resistance, and general polyolefins, such as LDPE, LLDPE, polypropylene, etc., can be used.

[0056] In the laminate for packaging bags of the present invention, the deodorizing adhesive layer functions as a laminate adhesive layer having deodorizing properties, and is therefore disposed between one of the layers constituting the laminate for packaging bags and another layer adjacent to the one layer.

[0057] The laminate for packaging bags of the present invention may have only one deodorant adhesive layer, or may have two or more deodorant adhesive layers. However, if the deodorant adhesive layer is disposed between appropriate layers of the laminate for packaging bags, the laminate for packaging bags can exhibit the desired deodorant performance even with only one layer.

[0058] In a packaging bag laminate including a substrate layer, a deodorant adhesive layer, and a sealant layer, the deodorant adhesive layer may be disposed on the inner side (the side of the contents) of the substrate layer and on the outer side of the sealant layer. An example of a packaging bag laminate of this embodiment is shown as a schematic cross-sectional view in Fig. 1. The packaging bag laminate (101) in Fig. 1 has a substrate layer (10), a deodorant adhesive layer (20), and a sealant layer (30) in this order.

[0059] In a laminate for a packaging bag which further includes one or two layers selected from a barrier layer and a reinforcing layer in addition to a base layer, a deodorizing adhesive layer, and a sealant layer, the deodorizing adhesive layer may be positioned on the inner side (the side of the contents) of the base layer and on the outer side of the sealant layer.

[0060] In a packaging bag laminate including a barrier layer, the deodorant adhesive layer may be disposed on the inner side (the side of the contents) of the barrier layer and on the outer side of the sealant layer in order to effectively exert the deodorant function. An example of a packaging bag laminate of this embodiment is shown as a schematic cross-sectional view in Fig. 2. The packaging bag laminate (102) in Fig. 2 has, in this order, a base layer (10), a laminate adhesive layer (40), a barrier layer (11), a laminate adhesive layer (40), a reinforcing layer (12), a deodorant adhesive layer (20), and a sealant layer (30).

[0061] <<Method for manufacturing laminate for packaging bag>> The laminate for packaging bags of the present invention may be produced by a method including using the deodorant adhesive of the present invention for bonding at least one layer of the laminate for packaging bags. Bonding between layers using the deodorant adhesive may be performed, for example, by a dry lamination method.

[0062] For example, the packaging bag laminate (101) shown in FIG. 1 may be produced by a method in which the interlayer adhesion between the base layer (10) and the sealant layer (30) is carried out by dry lamination using the deodorizing adhesive of the present invention as an adhesive, and a deodorizing adhesive layer (20) is formed between the base layer (10) and the sealant layer (30).

[0063] In addition, in the packaging bag laminate (102) shown in FIG. 2, the interlayer adhesion between the base layer (10) and the barrier layer (11), and between the barrier layer (11) and the reinforcing layer (12) are performed by dry lamination using a laminating adhesive in a known technology, and a laminating adhesive layer (40) is formed between these layers, respectively, but the interlayer adhesion between the reinforcing layer (12) and the sealant layer (30) is performed by dry lamination using the deodorizing adhesive of the present invention, and the packaging bag laminate (102) may be produced by a method in which a deodorizing adhesive layer (20) is formed between the base layer (10) and the sealant layer (30).

[0064] The laminating adhesive for forming the laminating adhesive layer (40) may be appropriately selected from, for example, ester-based, ether-based, etc. Since the laminate for packaging bags of the present invention is intended to heat treat the contents, a two-liquid type ester-based adhesive having excellent heat resistance is preferable as the laminating adhesive.

[0065] The laminate for packaging bags of the present invention can deodorize odors, particularly sulfur odors, emanating from the contents or the packaging bag, or both, when the laminate is heat-treated in a state in which the contents are sealed as a packaging bag. Therefore, the laminate for packaging bags of the present invention can be suitably applied to, for example, packaging bags for retort foods. Examples of retort foods include porridge, side dishes, nursing care foods, baby foods, etc.

[0066] The laminate for packaging bags of the present invention can also be used as a packaging bag for products that have a problem with the unpleasant odor that the substance itself has even without heating. Examples of such products include medicines, supplements, etc. Examples of medicines and supplements include vitamins, amino acid preparations, DHA / EPA-based preparations, garlic-based preparations, etc.

[0067] The laminate for packaging bags of the present invention can also be used as storage bags (such as laminate packs) for electrical and electronic devices that may be affected by outgassing (especially sulfur-based gases). Examples of such products include sulfide-based all-solid-state batteries. EXAMPLES

[0068] In the following Examples and Comparative Examples, the following adhesives and raw materials for the laminate for packaging bags were used, respectively.

[0069] {Adhesive raw materials} <Zeolite> Abscents 3000: Product name, high silica zeolite manufactured by Resonac Universal Co., Ltd., SAR=3,000, MFI type, average particle size 3-5μm (3,000-5,000nm) Nano ZSM-5: Crushed ZSM-5, SAR>20, MFI type, average particle size 50nm Zeoal-4A: Na-A type zeolite, SAR=1, LTA type, average particle size 50nm 4A: Na-A type zeolite, SAR=1, LTA type, average particle size 3-5μm (3,000-5,000nm)

[0070] <Transition metal doped zeolite> Zeoal-Ag: Nakamura Choukou Co., Ltd., "Zeoal (registered trademark) Ag", Ag-nano zeolite, Na-A type zeolite + 30-50 mol% of the ions are Ag + Ion-exchanged zeolite, SAR=1, LTA type, average particle size 50 nm Zeoal-Cu: Nakamura Choukou Co., Ltd., "Zeoal (registered trademark) Cu", Cu-nano zeolite, Na-A type zeolite + 60-90 mol% of the ions are Cu 2+ Ion-exchanged zeolite, SAR=1, LTA type, average particle size 50 nm Zeoal-Zn: Nakamura Choukou Co., Ltd., "Zeoal (registered trademark) Zn", Zn-nano zeolite, Na-A type zeolite + 20-40 mol% of the ions are Zn 2+ Ion-exchanged zeolite, SAR=1, LTA type, average particle size 50 nm

[0071] The above average particle size is a particle size at which the cumulative mass percentage is 50% in the particle size distribution obtained by a laser diffraction method measured in accordance with JIS Z8825:2022.

[0072] <Laminating adhesive> Mitsui Chemicals' two-component ester adhesive Main ingredient: Takelac (registered trademark) A-525 Hardener: Takenate (registered trademark) A-52

[0073] 《Laminated material raw material for packaging bags》 <Base material layer> PET(12): Polyethylene terephthalate film, thickness 12 μm

[0074] <Barrier layer> AL(9): Aluminum foil, thickness 9 μm

[0075] <Reinforcing layer> Ny(15): Nylon film, thickness 15 μm,

[0076] <Sealant layer> CPP(50): Unstretched polypropylene film, thickness 50μm Example 1 (1) Preparation of deodorant adhesive A deodorant adhesive was prepared by mixing 9 parts by weight of the main agent of the aliphatic ester-based two-liquid adhesive "Takelac A-525" and 1 part by weight of the hardener "Takenate A-52", as well as 16 parts by weight of ethyl acetate as a diluting solvent and 0.5 parts by weight of Zeoal-Ag as a deodorant (zeolite). The content of the deodorant (zeolite) in the obtained adhesive was 1.9% by weight.

[0077] (2) Formation of laminate for packaging bag A laminate for packaging bags having the following configuration was manufactured by the dry lamination method. At this time, for adhesion between Ny (15) and CPP (50), a deodorant adhesive layer was formed using the deodorant adhesive prepared above. For adhesion between other layers, a laminate adhesive layer not containing a deodorant was formed using the above-mentioned laminate adhesive. The coating amount of the deodorant adhesive was 3.5 g / m2. 2 (Deodorant amount 0.3g / m 2 ) was decided. PET(12) / / AL(9) / / Ny(15) / Deodorizing adhesive layer / CPP(50)

[0078] Here, " / / " indicates a laminating adhesive layer in a dry laminate.

[0079] In the above, the coating suitability when the deodorant adhesive was applied was evaluated according to the following criteria. A: When the coating layer was smooth C: When the coating layer is not smooth

[0080] (4) Evaluation The laminate for packaging bags obtained above was used to heat-seal the ends to form a packaging bag with an inner dimension of 100 mm x 40 mm. 10 mL of an L-cysteine ​​aqueous solution with a concentration of 300 ppm was sealed inside the packaging bag. The packaging bag after sealing was placed in a thermostatic chamber and heated at 120°C for 30 minutes. The hydrogen sulfide concentration in the L-cysteine ​​aqueous solution after heating was measured and a sensory test for sulfur odor was performed using the following methods.

[0081] (i) Measurement of hydrogen sulfide concentration The hydrogen sulfide concentration in the L-cysteine ​​aqueous solution after heating was measured using a simple water quality measuring device, "Pack Test Sulfide (Hydrogen Sulfide) WAK-S" manufactured by Kyoritsu Chemical Research Institute Co., Ltd.

[0082] (ii) Sensory test for sulfur odor After heating, the packaging bag was opened, and immediately after opening, panelists (evaluators) checked whether or not there was a sulfur odor in the packaging bag, and rated it on the following three-level scale. A: Has a sulfur smell B: Slight sulfur smell C: No sulfur smell

[0083] The number of panelists was five, and the result presented by the largest number of panelists was adopted as the evaluation result.

[0084] Examples 2 and 3, and Comparative Examples 1 to 5 Except for using the zeolite listed in Table 1, deodorizing adhesives were prepared in the same manner as in Example 1, and laminates for packaging bags were formed using these and evaluated. In Comparative Example 1, a laminate for packaging bags was produced and evaluated by using a laminating adhesive that did not contain a deodorizer instead of the deodorizing adhesive for bonding between Ny (15) and CPP (50).

[0085] The above results are summarized in Table 1.

[0086] [Table 1]

[0087] Referring to Table 1, the following can be seen:

[0088] The laminates of Comparative Examples 2 and 3, which contain a deodorizing adhesive layer formed using a hydrophobic zeolite with an SAR of more than 20 as a deodorizing agent, did not show any effect in reducing hydrogen sulfide concentration and sulfur odor compared to the laminate of Comparative Example 1, which does not have a deodorizing adhesive layer.

[0089] Furthermore, in the laminates of Comparative Examples 4 and 5, which contain a deodorizing adhesive layer formed using hydrophilic zeolite with an SAR of 20 or less but not doped with a transition metal, no reduction in hydrogen sulfide concentration or sulfur odor was observed compared to the laminate of Comparative Example 1.

[0090] Furthermore, the deodorant adhesives of Comparative Examples 2 and 5, which were prepared using zeolite with a large dispersed particle size, formed deodorant adhesive layers with insufficient smoothness.

[0091] In contrast, the laminates of Examples 1 to 3, which include a deodorant adhesive layer formed using hydrophilic zeolite with an SAR of 20 or less and doped with a transition metal, showed a significant effect of reducing the hydrogen sulfide concentration and sulfur odor compared to the laminate of Comparative Example 1. Furthermore, in Examples 1 to 3, nano-zeolite with a small dispersed particle size was used, and the deodorant adhesive containing this had excellent coatability, and the formed deodorant adhesive layer had high smoothness. [Explanation of symbols]

[0092] 10 Base material layer 11 Barrier layer 12 Reinforcement layer 20 Deodorizing adhesive layer 30 Sealant Layer 40 Laminating adhesive layer 101, 102 Laminate for packaging bags

Claims

1. A transition metal doped nano zeolite and an adhesive, Coating amount: 10.0 g / m 2 Below is the Deodorizing adhesive layer for packaging bags.

2. The deodorant adhesive layer according to claim 1 , wherein the nano zeolite has an average particle size of 5 nm or more and 500 nm or less.

3. The deodorant adhesive layer according to claim 1 , wherein the nano zeolite has an SAR of 20 or less.

4. The deodorant adhesive layer according to claim 2 , wherein the nano zeolite has an SAR of 20 or less.

5. The odor eliminating adhesive layer according to claim 1 , wherein the transition metal is one or more selected from Ag, Cu, and Zn.

6. The odor eliminating adhesive layer according to claim 1 , wherein the adhesive is one or two types selected from an ester-based adhesive and an ether-based adhesive.

7. An odor-eliminating adhesive comprising a transition metal-doped nanozeolite and an adhesive.

8. The deodorant adhesive according to claim 7, which is used to form the deodorant adhesive layer according to claim 1.

9. A laminate for a packaging bag, comprising a substrate layer, the odor eliminating adhesive layer according to claim 1, and a sealant layer.

10. The laminate for packaging bags according to claim 9, further comprising one or two layers selected from a barrier layer and a reinforcing layer.

11. A method for producing the packaging bag laminate according to claim 9 or 10, The method comprises using the deodorizing adhesive according to claim 7 for bonding at least one layer between the layers. A method for manufacturing a laminate for a packaging bag.

Citation Information

Patent Citations

  • Laminate for heat sterilization treatment, packaging material for heat sterilization treatment and package for heat sterilization treatment

    JP2019177518A

  • Odor scavenging laminate adhesive resin composition and package, and packaging structure

    JP2020164587A